Mapping 20 years of accessibility research in HCI: A co-word analysis. Issue 175 (July 2023) - Sarsenbayeva, Zhanna; van Berkel, Niels; Hettiachchi, Danula; Tag, Benjamin; Velloso, Eduardo; Goncalves, Jorge; Kostakos, Vassilis
Abstract: We employ hierarchical clustering, strategic diagrams, and network core–periphery analysis to assess and visualise the intellectual progress of accessibility research within HCI in the past two decades. The study quantifies and explains the development of accessibility research and its thematic evolution based on 1, 535 papers published at TACCESS, ASSETS, IJHCS, and CHI and their respective 3, 470 author-assigned keywords. The novelty of this work is based on employing a quantitative methodological approach to provide an overview of accessibility research progress and insights into its driving and trending themes through the period 2001–2021. In addition, we identify declining, emerging, and core backbone themes of accessibility research. Finally, we discuss the opportunities for research that arise from our findings. These contributions provide a roadmap for researchers working on accessibility.